Compartment syndrome of the deltoid: a case report of a common presentation in a rare location. Issue 4 (7th August 2016) - Harrison, Andrew; Sumner, Michael; Sobecki, Jeffrey; Christiansen, Gregory
ABSTRACT: Compartment syndrome presents with a slow onset of pain. Anything that causes an increased intra-compartmental pressure can lead to surgical emergency. A 45-year-old male presents to the emergency department with prolonged syncope. The patient is unable to recall the previous night except for using oxycodone. Patient medical history is significant for ischemic cardiomyopathy and myocardial infarction. Physical exam showed left arm pain and swelling, decreased sensation to light touch, and decreased range of motion. The left forearm was cool to touch with decreased pulses. Blood urea nitrogen/creatinine ratio was 47/4.0, white blood cell was 15.1, troponin was 34.2, and creatine kinase was immeasurable. Electrocardiogram showed non-specific T-wave abnormalities. Computed tomography showed left hemithoracic musculature enlargement. The patient's symptoms continued to worsen. The patient underwent emergency fasciotomy to relieve intra-compartmental pressure. Compartment syndrome of the deltoid is rare and yielded less than ten cases in our literature review. Although compartment syndrome usually affects the forearm, one must consider its possibility in any anatomical location.